Effect of the electric field at 50 Hz and variable intensities on biochemical markers in the honey bee's hemolymph. - Paweł Migdał (Public Library of Science (PLoS), 2021)
The amount of artificial electromagnetic fields of various parameters in the honey bee's environment increases globally. So far, it had been proven that exposure to an E-field at 50 Hz can cause changes in bee's behavior, alter the activity of proteases, and enzymatic antioxidants. Due to the potentially harmful effect of this factor on honey bees, we decided to investigate the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP), and the concentration of albumin and creatinine in bee's hemolymph after exposure to 50 Hz E-field. Honey bee workers were placed in wooden cages (200 × 150 × 70 mm) and exposed to the 50 Hz E-field with the intensity of <1, 5.0, 11.5, 23.0, or 34.5 kV/m for 1, 3, 6, or 12h. A homogeneous 50 Hz E-field was generated in the form of a plate capacitor. Hemolymph samples for analysis were taken immediately after the end of exposure to the E-field from 100 bees from each group. According to our study, the activity of AST, ALT, and ALP in honey bees' hemolymph decreased after exposure to 50 Hz E-field with various intensities. The decrease in AST, ALT, and ALP activity intensified with prolonged exposure time. 50 Hz E-field may cause the impairment of crucial metabolic cycles in the honey bees' organism (such as the citric acid cycle, ATP synthesis, oxidative phosphorylation, β-oxidation). Moreover, exposure to E-Field altered the concentration of creatinine and albumin, which are important non-enzymatic antioxidants. Such changes may indicate a disturbance in protein metabolism and increased muscle activity.